REOS, SMND, AND RBSR ISOTOPE EVIDENCE FOR THICK ARCHAEAN LITHOSPHERIC MANTLE BENEATH THE SIBERIAN CRATON MODIFIED BY MULTISTAGE METASOMATISM - Pearson D.G.; Shirey S.B.; Carlson R.W.; Boyd F.R.; Pokhilenko N.P.; Shimizu N. (My University, 1995)
A suite of peridotite xenoliths from kimberlites intruding the Siberian craton indicate the presence of lithospheric mantle over 150 km thick at 350 Ma. We report Sr-Nd isotope data for minerals from the peridotite xenoliths together with osmium isotopic compositions for whole-rocks and two olivine separates. Additionally, the osmium isotopic composition of a carbonatite from Fort Portal, Uganda, has been measured in order to evaluate the effect of carbonatite metasomatism on mantle Re-Os systematics.
Keywords: Archaean; Precambrian::Archean; Докембрий::Архей